Characterization of Antigenic Relatedness Among GI Norovirus Genotypes Using Serum Samples From Norovirus-Infected Patients and Mouse Sera - Xie, Dongjie; Chen, Junrui; Yu, Jingrong; Pei, Fuyu; Koroma, Mark Momoh; Wang, Lu; Qiu, Mengsi; Hou, Yuzhen; Yu, Dexian; Zhang, Xu-Fu; Dai, Ying-Chun (Frontiers in Microbiology, 2020)
Characterizing diversity and the antigenic relatedness of norovirus remains a primary focus in understanding its biological properties and vaccine designs. The precise antigenic and serological features of GI genotypes have not been studied. The study represented an investigation on a gastroenteritis outbreak related to GI.3 norovirus and the three most detected GI genotypes. GI.2 (belonging to immunotype B), GI.3 and GI.9 (belonging to immunotype C) were selected to characterize their phylogenetic relationship, HBGA binding profiles and antigenic relatedness within (intra-immunotypes) and between (inter-immunotypes) genotypes using mouse sera and patient’s serum samples from the GI.3 related outbreak. Wide HBGA binding profiles and evolution of binding affinity were observed in the three GI genotypes studied. A low specific blockade antibody to GI.3 in the population generated the pool of susceptible individuals and supported virus spread in the outbreak. We found strong blockade immune response in homologous strains, moderate intra-immunotypes blockade but weak inter- immunotypes blockade in humans following GI.3 norovirus infections. These findings further support the immunotypes grouping and will be valuable for optimizing the design of norovirus vaccine.